Two-stage reconstruction for flexor tendon injuries in zone II using a silicone rod and pedicled sublimis tendon graft - Abdul-Kader Mohammed; Amin Mahmound (Indian Journal of Plastic Surgery, 2010)
We report the results of staged flexor tendon reconstruction in 12 patients (12 fingers) with neglected or failed primary repair of flexor tendon injuries in zone II. Injuries involved both flexor digitorum profundus (FDP) and flexor digitorum sublimis (FDS), with poor prognosis (Boyes grades II-IV). The procedure included placing a silicone rod and creating a loop between the FDP and FDS in the first stage and reflecting the latter as a pedicled graft through the pseudosheath created around the silicone rod in the second stage. At a mean follow-up of 18 months (range 12-30 months), results were assessed by clinical examination and questionnaire. The mean total active motion of these fingers was 188o. The mean power grip was 80.0% and pinch grip was 76% of the contralateral hand. The rate of excellent and good results was 75% according to the Buck-Gramcko scale. These results were better than the subjective scores given by the patients. Complications included postoperative hematoma in two, infection in one, silicone synovitis in one (after stage I) and three flexion contractures after stage II. This study confirmed the usefulness of two-stage flexor tendon reconstruction using the combined technique as a salvage procedure to restore flexor tendon function with a few complications.